Smartphone Addiction, Children's Mental Health, and the Role of Parenting - Reza Fajar Amalia; Achir Yani Syuhaimie Hamid (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Increased smartphone utilization by children will increase the risk of addiction which consequently affecting the physical and mental health status of children. This impact requires an appropriate prevention strategies and involves the family or parents as important social support system for child's development. This study aim to identify systematically the effects of smartphone addiction on children, addiction prevention strategies, and formulation of guideline for parents in assisting their children when using smartphones. This study using systematic review by searching articles in electronic database (SpringerLink, ClinicalKey, SAGE Publication, Annual Reviews). The keywords used are